Asymmetry of frameshift mutagenesis during leading and lagging-strand replication in Escherichia coli - Gawel, Damian; Jonczyk, Piotr; Bialoskorska, Malgorzata; Schaaper, Roel M; Fijalkowska, Iwona J (Mutation research, 2002)
Mutations in DNA, including frameshifts, may arise during DNA replication as a result of mistakes made by the DNA polymerase in copying the DNA template strands. In our efforts to better understand the factors that contribute to the accuracy of DNA replication, we have investigated whether frameshift mutations on the Escherichia coli chromosome occur differentially within the leading and lagging-strands of replication. The experimental system involves measurement of the reversion frequency for several defined lac frameshift alleles in pairs of strains in which the lac target is oriented in the two possible directions relative to the origin of chromosomal replication. Within these pairs any defined lac sequence will be subject to leading-strand replication in one orientation and to lagging-strand replication in the other. Fidelity differences between the two modes of replication can be observed as a differential lac reversion between the two strains. Our results, obtained with a series of lac alleles in a mismatch-repair-defective background, indicate that for at least some of the alleles there is indeed a difference in the fidelity of replication between the two modes of replication.